Efficiency Comparison Of Direct DC-AC Power Conversion System And Conventional Power Conversion Systems - Hamidi, Muhammad Najwan (Universiti Sains Malaysia, 2018)
Multilevel inverters are gaining popularity especially in medium to high power applications. Today, direct DC-AC inverters with the like of cascaded H-Bridge and modular multilevel (MML) Half-Bridge configuration are becoming much more accepted due to their vast advantages compared to older conventional inverter configurations such as neutral-point clamped and flying-capacitor inverter. This study focussed on efficiency comparison between these direct DC-AC inverter and conventional inverter topologies based on grid link application. The purpose is to get a clear overview of the performance of tested inverter topologies. The efficiency evaluation was fully performed by using PSIM simulation software package. For every selected inverter topology, the output power, DC link voltage, semiconductor devices configurations and pulse width modulation (PWM) method were kept constant for a fair comparison between them. In controlling the power, real power-reactive power (PQ), proportional-integral (PI) based direct-quadrature (DQ) control scheme was implemented in all selected topologies. As for the PWM method, In Phase Disposition Level Shifted PWM (IPDPWM) was used since it produces decent output harmonic performance with minimum components. From the simulations, it was observed that direct DC-AC inverters have better efficiency performance in overall compared to conventional DC-AC inverters where their minimum efficiencies were around 98.3 % and able to reached up to 99.1 %. On the other hand, conventional DC-AC inverters’ efficiencies ranged from 98.1 % to 99.0 %.